A Review on Commercially Available Anthropomorphic Myoelectric Prosthetic Hands, Pattern-Recognition-Based Microcontrollers and sEMG Sensors used for Prosthetic Control - Calado, Alexandre (2019)
It has been reported that over 3 million individuals live with upper limb amputation worldwide. Losing a hand drastically reduces the individual's quality of life. Fortunately, there are several prosthetic solutions available in the market that try to restore some of the missing hand's functions and characteristics. This paper presents a review on three of the main components of a typical transradial myoelectric prosthesis that can be found in the market. The goal was to provide the reader with an overview of commercially available anthropomorphic myoelectric prosthetic hands with high degrees of freedom, pattern-recognition-based microcontrollers and sEMG sensors used for prosthetic control.